2023
DOI: 10.1038/s41467-023-35808-6
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering genetic causes for sex differences in human health through drug metabolism and transporter genes

Abstract: Sex differences have been widely observed in human health. However, little is known about the underlying mechanism behind these observed sex differences. We hypothesize that sex-differentiated genetic effects are contributors of these phenotypic differences. Focusing on a collection of drug metabolism enzymes and transporters (DMET) genes, we discover sex-differentiated genetic regulatory mechanisms between these genes and human complex traits. Here, we show that sex-differentiated genetic effects were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…It is well known that the genetic polymorphism of CYP enzymes has the potential to impact the systemic exposure of many drugs. 29 For ATX, the final PK model estimated a lower ATX bioavailability in CYP2D6 AS ≥ 1 patients as compared with the CYP2D6 AS 0 and 0.5 patients following a single oral dose of 0.5 mg/kg (Table 1). The estimated ATX bioavailability in the CYP2D6 AS ≥ 1 groups were 89.5% and 81.2% of that in the CYP2D6 AS 0 and 0.5 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the genetic polymorphism of CYP enzymes has the potential to impact the systemic exposure of many drugs. 29 For ATX, the final PK model estimated a lower ATX bioavailability in CYP2D6 AS ≥ 1 patients as compared with the CYP2D6 AS 0 and 0.5 patients following a single oral dose of 0.5 mg/kg (Table 1). The estimated ATX bioavailability in the CYP2D6 AS ≥ 1 groups were 89.5% and 81.2% of that in the CYP2D6 AS 0 and 0.5 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is a method to assess the presence of a shared causal variant in the region for two traits. Analysis was performed using the coloc R package with PPH4 > 0.5 as the threshold for the shared genetic effects between the two traits [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified that many drug metabolism genes have sex-biased gene expression in the liver [14][15][16][17], so we chose to investigate sex-specific liver gene-regulatory networks to determine if there are potential gene regulation differences of drug metabolism genes between males and females in the liver.…”
Section: The Gene-regulatory Network Neighborhoods Around Drug Metabo...mentioning
confidence: 99%
“…Multiple studies have found sex differences in several pharmacokinetic metrics, such as the area under the curve of the plasma concentration of a drug versus time after dose or peak/maximum concentration [11]. Other studies have shown that many drug metabolism enzymes have differential gene expression and protein activity in male and female liver tissue [14][15][16]. Additionally, Oliva, et al showed that in the Genotype-Tissue Expression (GTEx) project (n = 16,245 RNA-sequencing samples across 44 human tissues), 37% of genes had sex-biased tissue-specific expression and that these genes were enriched in drug metabolism gene sets (i.e., Gene Ontology [GO] and Kyoto Encyclopedia of Genes and Genomes [KEGG] terms: "Xenobiotic Metabolism, Mitochondrial Genes and Fatty Acid Oxidation," " Cellular Response to Hormones and Drugs," "Drug Interaction and Response," and "Drug Interaction") [17].…”
Section: Introductionmentioning
confidence: 99%